POTENSI MAKAM PERMATA SAPIHAK TERHADAP KEHIDUPAN MASYARAKAT DESA BINABO JULU, KECAMATAN BARUMUN KABUPATEN PADANG LAWAS TAHUN (2015-2018) - surya apso daulay (Pendidikan Sejarah, 2019)
Abstract This study aims to describe of existence of Makam Sapihak toward life of the community of Binabo Julu village, Barumun sub-district, Padang Lawas District, 2015-2018. The approach of the research used descriptive qualitative interview was conducted in collecting the data. The result of the research was 1) existence of Makam Sapihak since a long time ago but the community did not really care about it and the community care Makam Sapihak sice 2015, 2) the influence of Makam Sapihak toward the community around there included social sector (the existence of community organizations around to care again the Makam Sapihak), economic sector (the creation entrepreneurship of where the community around them makes Makam Sapihak as a tourist attraction), culture sector (creating a culture or tradition of pilgrimage or visiting the Makam Sapihak), and 3) there is government involvement in the preservation of the Sapihak Grave. Key words: Makam Sapihak potential, social, economic, culture, 2015-2018